The role of probiotic on alveolar bone resorption - Desi Sandra Sari; Zahara Meilawaty; M. Nurul Amin (Dental Journal (Majalah Kedokteran Gigi), 2011)
Background: Probiotics are microbes derived from the group of lactic acid bacteria that work to maintain the health of hosts. Probiotics can also be used to improve oral health. Periodontal disease is usually marked with gingival inflammation and alveolar bone resorption. Gram negative anaerobic bacteria that play important role in human periodontal disease are Porphyromonas gingivalis. (P. gingivalis). P. gingivalis is a virulent bacteria in vivo or in vitro, and mostly found in subgingival plaque of periodontitis patients. Purpose: This study is aimed to know the role of probiotics to inhibit the resorption of alveolar bone induced with P. gingivalis. Methods: This study used male wistar rats divided into 4 groups. Group I was control group (without treatment); group II was induced with P. gingivalis ATCC 33277 for 5 days; group III was induced with P. gingivalis ATCC 33277 and also injected with probiotics (Lactobacillus casei ATCC 4224) for 5 days simultaneously; and group IV was induced with P. gingivalis ATCC 33277 for 5 days and also injected by probiotics (Lactobacillus casei ATCC 4224) in the next 5 days. After that, the samples were decapitated, taken their alveolar bone, and then were examined by immunohistochemistry to observe osteoclast activity in alveolar bone resorption by using tartrate-resistant acid phosphatase (TRAP) expression. All data were then analyzed statistically. Results: It is known that there were significant differences of TRAP expression among all those treatment groups (p < 0.05). Conclusion: It then can be concluded that probiotics can decrease osteoclast activity in periodontal tissue of wistar rats, so it can inhibit alveolar bone resorption.Latar belakang: Probiotik adalah mikroba dari golongan bakteri asam laktat yang bekerja mempertahankan kesehatan host dan probiotik dapat digunakan untuk meningkatkan kesehatan rongga mulut. Penyakit periodontal ditandai dengan adanya keradangan pada gingiva dan resobsi tulang alveolar. Bakteri Gram negatif anaerob yang sangat berperan dengan penyakit periodontal pada manusia adalah Porphyromonas gingivalis (P. gingivalis). P. gingivalis merupakan bakteri yang virulen, baik diuji secara in vivo maupun in vitro, dan banyak ditemukan pada plak subgingiva penderita periodontitis. Tujuan: Penelitian ini bertujuan untuk mengetahui peran probiotik dalam menghambat resorbsi tulang alveolar yang diinduksi P.gingivalis. Metode: Penelitian ini memakai tikus jenis wistar jantan sebagai sampel dan dibagi menjadi 4 kelompok: Kelompok I yaitu kontrol tanpa perlakuan; kelompok II di induksi P.gingivalis ATCC 33277 selama 5 hari; Kelompok III di induksi P.gingivalis ATCC 33277 ditambah suntikan probiotik (Lactobacillus casei ATCC 4224) selama 5 hari secara bersamaan; dan Kelompok IV di induksi P.gingivalis ATCC 33277 selama 5 hari ditambah suntikan probiotik (Lactobacillus casei ATCC 4224) 5 hari selanjutnya. Setelah itu sampel didekaputasi, diambil tulang alveolar dilakukan pemeriksaan imunohistokimia untuk melihat aktivitas osteoklas dalam resopsi tulang alveolar dengan mendeteksi tartrate-resistant acid phosphatase (TRAP). Data yang dikumpulkan dianalisis secara statistik. Hasil: Terdapat perbedaan yang bermakna antar kelompok untuk ekspresi TRAP (p < 0.05). Kesimpulan: Dapat disimpulkan bahwa probiotik dapat menurunkan aktivitas osteoklas pada wistar tikus yang mengalami periodontitis sehingga dapat mencegah resorbsi tulang alveol.